Role of Nanofillers on Mechanical and Dry sliding Wear Behavior of Basalt- Epoxy Nanocomposites. (2017) - Mahesha, C R; Shivarudraiah,; Mohan, N; Rajesh, M
Abstract: Basalt fiber reinforced polymer composites are nowadays creating attention in both industrial and academic world. New developments are still under way to explore the application of these composites by tailoring their properties. The objectives of this research article is to evaluate the effect of the incorporation of Nano titanium dioxide (TiO2 ) alone and in combination with nano clay on the mechanical and tribological wear behaviour of Basalt fabric– Epoxy (BE) composites. A vacuum-assisted resin infusion technique (VARI) was employed to obtain a series of BE composites. The mechanical properties, including tensile strength, tensile modulus, elongation at break, and surface hardness, were investigated in accordance with ASTM standards. From the experimental investigation, it was found that the tensile strength and dimensional stability of the B–E composite increased with increasing fillers. The effect of different loads (10 to 30 N) and sliding distances from 2000 to 8000 m on the performance of the wear resistance of the composites were measured. Slight increase in coefficient of friction for nano Clay-BE composite, reduction of coefficient of friction was noticed for the nano TiO2 and TiO2/Clay filler filled composites. The wear loss of the composites decreased with addition of fillers and increased with increasing sliding distance. Failure mechanisms of the worn surfaces of the filled and unfilled composites were examined with SEM.